Protection of copyright in E-commerce within the European Union. Analysis of legal issues with respect to download of musical works - Kuzmina, Ksenija (Riga Graduate School of Law, 2019)
Stricter and better - defined protection mechanism for copyright issues as well as adaptation and harmonization of the national and community jurisdiction to the changes became a necessity because of proceeding rapid technological development and its increased importance in community trade as it became a major reason for negative tendency in the functioning of the Internal Market. Doctrinal research method will be mostly used in a process of thesis development because the nature of enforcement of the copyright concerning activity online as it currently lays down within its legislative framework, outcoming case-law and its interpretation. Scope of the analysis will remain within the European Union countries and its jurisdiction. Results showed correlation between development of the digital environment and increased frequency of cases on copyright abuse providing that unlawful download of a musical works remains one of the most commonly infringed type of Intellectual Property.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Copyright